Traditional Taste and Economic Potential: Tangerang's Local Snack-Based Culinary Tourism - Yanti, Lia Dama; Susanti, Metta; Wibowo, Susanto (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
This study investigates the connection between Tangerang's traditional flavor and the economic potential of culinary tourism centered around local snacks. The potential of Tangerang's distinctive culinary wealth to boost regional economic development has not been fully realized. To gain a thorough grasp of the phenomenon, this study employs a mixed methods approach that blends qualitative and quantitative techniques. While a survey of Tangerang tourists was used to get quantitative data, in-depth interviews with traditional culinary MSME players in Tangerang were used to gather qualitative data. The Structural Equation Modeling (SEM) technique of study demonstrates that the quality and authenticity of traditional flavors have a major impact on visitor happiness, which in turn has a beneficial effect on both the number of visitors and the revenue generated by local vendors. The study's findings give policymakers fresh perspectives when creating initiatives and regulations that encourage Tangerang's creative economy and culinary tourism to flourish. It is believed that Tangerang can boost its appeal as a culinary tourism destination and promote sustainable creative economic growth by using local knowledge and creating a thorough marketing plan. Keywords : Traditional flavors; Economic potential; Culinary tourism; Local snacks; Tangerang City